Profiling of volatile compounds in four Egyptian date cultivars - T. G. Abedelmaksoud; M. A. Hassan; M. T. M. Assous; A. E. R. M. Khalaf-Allah (Пищевые системы, 2025)
Volatile compound plays an important role in consumers’ satisfaction and influences further consumption of the date fruit. Thus, the study analyzed the volatile compounds of three date fruit cultivars: Barhy, Samani, Zaghloul at khalal stage of ripeness (complete color) and Siwi at tamr stage of ripeness using solid-phase microextraction (SPME) in conjunction with gas chromatography-mass spectrometry (GC–MS). A total of 69 compounds were identified, including aldehydes, alcohols, esters, terpenoids, ketones, hydrocarbons, alkanes, and ethers. Barhy dates featured high levels of aldehydes, saturated hydrocarbons, volatiles, ethers, ketones, and esters. Zaghloul dates predominantly contained aldehydes, ethers, and ketones, while Samani dates were rich in ketones, aldehydes, esters, and ethers. Key compounds such as β-(Z)-2-butenal and β-methyl ionone were identified as significant contributors to the distinctive peculiar aromas of these date varieties. Notably, the Siwi variety exhibited a distinctive profile with prominent ethers, aldehydes, ketones, and esters. The Siwi variety contained the highest number of flavour compounds (48), followed by Zaghloul (25), Barhy (20), and Samani (19). This comprehensive analysis reveals a complex and varied aromatic compounds profile among the date cultivars, with each variety having its unique sensory characteristics. The results provide valuable insights into the volatile profiles of Egyptian date varieties, potentially guiding the production of date-derived products and thus enhancing their application in food processing industries.